2008
DOI: 10.1083/jcb.200809113
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic tone mediates leptin's inhibition of insulin secretion by modulating osteocalcin bioactivity

Abstract: The osteoblast-secreted molecule osteocalcin favors insulin secretion, but how this function is regulated in vivo by extracellular signals is for now unknown. In this study, we show that leptin, which instead inhibits insulin secretion, partly uses the sympathetic nervous system to fulfill this function. Remarkably, for our purpose, an osteoblast-specific ablation of sympathetic signaling results in a leptin-dependent hyperinsulinemia. In osteoblasts, sympathetic tone stimulates expression of Esp, a gene inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
189
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(201 citation statements)
references
References 26 publications
3
189
2
1
Order By: Relevance
“…From a mechanistic point of view, islet perifusion assays showed that osteocalcin acts as an insulin secretagogue [3]. Gene expression analyses of islets or cultured beta cell lines further demonstrated that osteocalcin directly enhances the expression of the insulin genes as well as those encoding cyclindependent kinase 4 (Cdk4), cyclin D1 (Ccnd1) and D2 (Ccnd2) [1][2][3]. These findings explain the positive effect that osteocalcin has on both insulin production and beta cell proliferation.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…From a mechanistic point of view, islet perifusion assays showed that osteocalcin acts as an insulin secretagogue [3]. Gene expression analyses of islets or cultured beta cell lines further demonstrated that osteocalcin directly enhances the expression of the insulin genes as well as those encoding cyclindependent kinase 4 (Cdk4), cyclin D1 (Ccnd1) and D2 (Ccnd2) [1][2][3]. These findings explain the positive effect that osteocalcin has on both insulin production and beta cell proliferation.…”
Section: Introductionmentioning
confidence: 60%
“…Conversely, the subcutaneous infusion of recombinant osteocalcin into wild-type mice causes an increase in blood insulin levels, enhances glucose tolerance and improves insulin sensitivity [2]. From a mechanistic point of view, islet perifusion assays showed that osteocalcin acts as an insulin secretagogue [3]. Gene expression analyses of islets or cultured beta cell lines further demonstrated that osteocalcin directly enhances the expression of the insulin genes as well as those encoding cyclindependent kinase 4 (Cdk4), cyclin D1 (Ccnd1) and D2 (Ccnd2) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…As with all endocrine loops, such a feedforward mechanism implies the existence of a break, and leptin represents at least one putative break that inhibits insulin secretion by inhibiting osteocalcin activity. (12) …”
Section: Insulin a Peripheral Link Between Bone Remodeling And Energmentioning
confidence: 99%
“…The osteoblast-specific protein osteocalcin regulates glucose handling through effects on insulin secretion and sensitivity (33). This action is in turn mediated by the adipokine leptin, which inhibits insulin secretion through direct effects on pancreatic ␤-cells (18) and through inhibition of osteocalcin activity (25). The interplay between bone and metabolism has recently been further elucidated by the discovery that the Forkhead family transcription factor FoxO1, a key regulator of insulin handling in multiple tissues, also acts within the osteoblast to control osteocalcin expression and bioactivity (46).…”
mentioning
confidence: 99%